Perencanaan Peningkatan Kapasitas Mesin Penanam Padi Berbasis Sintesis Kinematika Dan Dinamika - Silalahi, Samuel Tabah Penemuan Parulian; Wijianto, Agus; Zaira, Jupri Yanda; Ma'a, Mustaza (IRA Jurnal Teknik Mesin dan Aplikasinya (IRAJTMA), 2025)
Rice is a food crop commodity that plays a vital role in the Indonesian economy. The results of this study indicate that the designed system is capable of consistently maintaining a 25 cm spacing between seedlings through the harmonic motion of the planting arm. The angular and linear movements of the entire linkage are stable and periodic, resulting in a uniform planting process. The angular velocity of the main shaft is recorded as constant, supporting rotational stability, while the maximum motor torque is within a realistic range for field applications. The system also demonstrates good mechanical efficiency, characterized by stable kinetic energy of the rotational components and controlled motor power consumption. These findings have practical significance for practitioners and the agricultural machinery industry, as they can serve as a reference for the development of rice transplanters that are more energy efficient, highly precise, and suited to rice field conditions in Indonesia, thus potentially increasing productivity and reducing reliance on manual labor.